Efeito de pré-tratamentos: desidratação osmótica assistida com ultrassom e luz ultravioleta pulsada na secagem e qualidade da manga - Braga, Thayane Rabelo (2016)
Brazil is a country that stands out in fruit production, mainly in the export of some fruits, such as mango, which is appreciated by consumers for their sensory and nutritional characteristics. However so conservation methods are used to increase the shelf life of the product and add value, such as drying, along with pre-treatments that can act in preserving nutritional quality and aid in water loss (using osmotic dehydration) to reduce the drying time. Ultrasound and pulsed ultraviolet light are technologies that can affect the composition of foods either positively or negatively. On the context, the aim of this study was to evaluate the effect of pretreatment (dehydration using ultrasound and pulsed ultraviolet light) on the drying and preservation of quality of nutrients of dehydrated mango cubes. The samples were dried in an oven at 60 ° C, separated in control samples (in natural mango), but without dehydrated sample pre-treatments and specimens were subjected to ultrasound five times and four different concentrations of osmotic solutions. For the pulsed ultraviolet light, the samples were submitted to five radiation dosages. Color parameter assessments were performed, moisture variation, solid variation, water diffusivity, time to 90% reduction of water, electrolyte leakage, enzyme activity (PPO, POD, PME and PAX), hydrogen peroxide, vitamins water soluble (B1, B2, B3, B5, B6, and C) and soluble (A, D and E), pigments (carotenoids and β-carotene), phenolics and antioxidant activity (DPPH method). The use of ultrasound and pulsed ultraviolet light was effective in the inactivation of polyphenol oxidase and ascorbate oxidase enzyme treatments used in most conditions. Using these pre-treatments the amount of hydrogen peroxide was increased, and thus the antioxidant capacity and phenolics also showed an increase for some process conditions. Vitamins B and C were degraded with the use of pre-treatments, but this degradation had a greater influence on the drying process, and therefore these technologies are set to minimize the loss of vitamins B1, B2, B3, B5 and C, as well as carotenoids β-carotene, and pigments. Other B6 vitamins A, D and E. which losses obtained with the use of sonication and p UV-radiation. For the color parameters of the samples subjected to pre-treatments on study, decreased only when compared with the sample in nature. Ultrasound and ultraviolet light does not influence the color change of the sleeve as heat treatment. Osmotic dehydration is indicated as pre-drying treatment with ultrasound, since it helps in further loss of water, as well as ultraviolet light. What are not thermal technologies which favor an increase in water diffusivity, and thus can be suitable for reducing the drying time